The ecologically relevant genetics of plant–plant interactions. (January 2023) - Becker, Claude; Berthomé, Richard; Delavault, Philippe; Flutre, Timothée; Fréville, Hélène; Gibot-Leclerc, Stéphanie; Le Corre, Valérie; Morel, Jean-Benoit; Moutier, Nathalie; Muños, Stéphane; Richard-Molard, Céline; Westwood, James; et al.
Abstract : Interactions among plants have been long recognized as a major force driving plant community dynamics and crop yield. Surprisingly, our knowledge of the ecological genetics associated with variation of plant–plant interactions remains limited. In this opinion article by scientists from complementary disciplines, the international PLANTCOM network identified four timely questions to foster a better understanding of the mechanisms mediating plant assemblages. We propose that by identifying the key relationships among phenotypic traits involved in plant–plant interactions and the underlying adaptive genetic and molecular pathways, while considering environmental fluctuations at diverse spatial and time scales, we can improve predictions of genotype-by-genotype-by-environment interactions and modeling of productive and stable plant assemblages in wild habitats and crop fields. Highlights: A better understanding of plant community diversity, productivity, and stability relies on deciphering the ecological genetics and molecular bases of plant–plant interactions in wild and crop species, which range from competitive to positive interactions. Compared with other categories of biotic interactions, we have limited knowledge of the genetics associated with natural variation of plant–plant interactions. Interdisciplinary projects are needed to explore the genetic and molecular underpinnings of key interacting phenotypic traits involved in plant–plant interactions, at complementary observation scales in a complex biotic and abiotic environment. Our future knowledge on the genetics of plant–plant interactions can fuel models aimed at predicting the best performing and/or stable plant assemblages, leading to alternative and eco-friendly agricultural systems.